School Counseling Programs Identifying Academic Development Needs - Parzych, Jennifer L.; Generali, Margaret; Yavuz, Olcay (Journal of Education, 2021)
This study examined student, parent, and faculty perceptions of academic development needs and related comprehensive school counseling program services from four urban middle and high schools. Participants (n = 1,032) completed a survey designed to assist schools in planning and evaluating their career and college readiness programs, and exploring perceived student support needs. Statistically significant differences were observed in stakeholder perceptions among 12 identified interventions that support improved academic development, through factorial analysis of variance (ANOVA) and pairwise comparisons analysis. Findings provide valuable information about prioritizing student academic counseling services strategically and effectively, to meet program needs of students in high-poverty schools.
Keywords: academic development; college readiness; dept.csp; dept.edl; peer-reviewed; poverty; school counselors

Implementing the developmental school counseling core curriculum in the classroom - Perusse, R.; Parzych, Jennifer L.; Erford, Bradley T. (Transforming the School Counseling Profession, 2018)
Transforming the way thousands of professional school counselors approach their work with students Transforming the School Counseling Profession demonstrates how to effectively implement systemic, data-driven school counseling programs.This clearly written text presents the profession in easy-to-understand language, and is illustrated with numerous applied examples, case studies, and vignettes. The 5th Edition has been updated to include all of the latest CACREP, ASCA, and ACA standards. It also now includes the DSM-5. Coverage of cultural competence has been expanded throughout the book. Also available with MyLab Counseling MyLab is the teaching and learning platform that empowers you to reach every student. By combining trusted author content with digital tools and a flexible platform, MyLab personalizes the learning experience and improves results for each student. MyLab Counseling organizes all assignments around essential learning outcomes and the CACREP standards–enabling easy course alignment and reporting. Note: You are purchasing a standalone product; MyLab Counseling does not come packaged with this content. Students, if interested in purchasing this title with MyLab Counseling, ask your instructor to confirm the correct package ISBN and Course ID. Instructors, contact your Pearson representative for more information. If you would like to purchase both the physical text and MyLab Counseling, search for: 0134669843 / 9780134669847 Transforming the School Counseling Profession plus MyLab Counseling with Enhanced Pearson eText -- Access Card Package Package consists of:       0134610598 / 9780134610597 Transforming the School Counseling Profession 0134642651 / 9780134642659 MyLab Counseling with Enhanced Pearson eText -- Access Card -- for Transforming the School Counseling Profession
Keywords: dept.csp